Territorial analysis of Aedes aegypti distribution in two Colombian cities: a chorematic and ecosystem approach - Mauricio Fuentes-Vallejo; Diana Rocío Higuera-Mendieta; Tatiana García-Betancourt; Lucas Andrés Alcalá-Espinosa; Diana García-Sánchez; David Alejandro Munévar-Cagigas; Helena Luisa Brochero; Catalina González-Uribe; Juliana Quintero (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
A territorial analysis of Aedes aegypti density was conducted in two Colombian cities using an ecosystem and chorematic approach. Entomological and behavioral data (by cluster) and information on the urban context were used to analyze the relationship between territorial structures and dynamics and vector density. The results were represented in graphic (chorematic) models. Arauca showed higher vector density than Armenia. Higher density was related to unplanned urbanization, flood-prone areas, low socioeconomic strata, household water tanks, higher temperature, and recall of control measures for adult mosquitos. Zones with low density indices coincided with diverse socioeconomic, ecological, and behavioral conditions. The study found a relationship between territorial structures and dynamics and vector density in both Arauca and Armenia, where the interaction between ecological and social systems shape areas with high and low A. aegypti density.